Estimating staffing requirements using workload indicators of staffing need at Braun District Hospital in Morobe Province, Papua New Guinea - Dixon Dimiri; Nelson Mek; Mary Therese Apini; Thelma Ali; Grace Turi Pumuye; Varage John Laka; Rosemary Jogo; Pamela Kari; Deki; Okech Mollent; Dapeng Luo; Anna Maalsen; et al. (BMC, 2022)
Abstract Background Papua New Guinea has seen some improvements in health indicators over the past years, but the pace of improvements is not as robust as expected. The Health Services Plan for Braun District Hospital redevelopment identified the importance of reflecting the hospital's role in the broader health system, particularly in upgrading the services to service a bigger population. In August 2020, the hospital was upgraded from a health centre-level 3 to a district hospital level 4. The need for assessing human resources for health requirements for this level of care was thus necessary. Methods The National Department of Health approved the use of the workload indicators of staffing need as the best tool to support in estimating staff requirements for the newly upgraded hospital. The focus was on clinical and non-clinical staff. Using already developed workload components and activity standards by the expert working groups for level 4 facilities, we visited the facility and collected data through interviews with the Lutheran Health Services representative, hospital management and staff. The technical task force reviewed daily registers, monthly reports and the data in the electronic national health information systems. The information collected was analysed using the workload indicators of staffing need software and interpreted. Results There were staffing shortages among the clinical staff like the medical officers, nursing officers, health extension officers, pharmacists, radiology staff unit and in the laboratory staff. Shortages among the non-clinical staff were recorded by the cashiers, security officers, drivers and boat skippers. The results showed that the facility lacks a medical laboratory technologist, pharmacists and a medical imaging technologist. The community health workers in this facility are utilized in all the areas where shortages are registered to multitask. Conclusion The results from this WISN study provide evidence for basing staffing decisions on. The WISN results from Braun District Hospital show that the facility requires a total of 33 inpatient nurses against the existing 21 inpatient nurses thus giving a staff gap of − 12 and a WISN ratio of 0.67. It is thus recommended that the hospital management prioritizes recruitment of nurses or if no resources, reassign one of the outpatient nurses to alleviate the pressure among the inpatient nurses or the extra theatre nurses to offer some services in the inpatient wards. WISN results can help managers make decisions such as change of health facility status from a health centre to a district hospital.